Youth NEET in Indonesia: Regional Disparities and Urban Planning Implications for Malang - Priyambodo, Reza Nugraha Dinda; Riyanto, Wahyu Hidayat; Putranto, FX Gugus Febri; Firmansyah, Muhammad (PANGRIPTA, 2026)
The phenomenon of youth Not in Employment, Education, or Training (NEET) poses a serious challenge to human resource development in Indonesia due to its long-term social and economic impacts. This study examines the NEET youth aged 16–30 by considering individual and environmental characteristics, including marital status, age, disability, education level, gender, region of residence, economic growth, and the interaction between marital status and age group. The study uses a quantitative approach, employing binary logistic regression, drawing on SAKERNAS 2023 data and economic growth data from 34 Indonesian provinces. The results show that all variables are significant at the 1 percent level (p < 0.01). Unmarried youth, younger individuals, people with disabilities, women, those with low education, and those residing in urban areas have a higher risk of being NEET. Education significantly reduces this risk. Economic growth has a limited, non-inclusive effect, and the interaction between marital status and age group reduces the probability of NEET status. This research contributes to the growing literature on regional development and planning through spatial disparities, particularly the urban-rural divide that contributes to the NEET phenomenon. The results demonstrate that place-based policies, such as strengthening the integration between education and the labor market, creating specific employment programs tailored to regional conditions, and implementing targeted interventions in rapidly growing urban areas like Malang City, are necessary to promote inclusive youth integration into the labor market.